PENGARUH KOMUNIKASI ORGANISASI DAN KOORDINASI TERHADAP KINERJA KARYAWAN PADA PT. BPR FIANKA REZALINA FATMA PEKANBARU - Gunawan, Hadi; Zulhaida, Zulhaida (Indonesian Journal of Business Economics and Management, 2022)
The purpose of this study was to determine the effect of organizational communication and coordination on employee performance at PT. BPR Fianka Rezalina Fatma Pekanbaru. Respondents in this study amounted to 40 people using the census method. The data analysis in this research is quantitative using multiple linear regression method and the data is analyzed using the SPSS program. Based on the results of this research shows that organizational communication and coordination have a partial effect on employee performance at PT. BPR Fianka Rezalina Fatma Pekanbaru. Simultaneously, organizational communication and coordination variables have a significant effect on employee performance variables at PT. BPR Fianka Rezalina Fatma Pekanbaru. The R Square value of 0.900 or 90% means that the employee performance variable is influenced by organizational communication and coordination while the remaining 10% is influenced by other variables not used in this study.